PROBLEM IMPLEMENTASI ASESMEN KOMPETENSI MINIMUM DI MADRASAH IBTIDAIYAH DAN SEKOLAH DASAR - Patimah, Patimah; Syamsi, Atikah; Fadia, Lulu (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2023)
The Minimum Competency Assessment (AKM) is a new policy initiated by the Ministry of Education and Culture. The Minimum Competency Assessment (AKM) a computer-based assessment that measures literacy and numeracy. The main key in the implementation of the Minimum Competency Assessment (AKM) is the teacher because the teacher is directly involved in the learning process. This research focuses on descriptive qualitative research.The purpose of this study is to describe the readiness of class V teachers for the Minimum Competency Assessment (AKM) in MI and SD. The techniques used in this qualitative research are by observing the implementation of the Minimum Competency Assessment (AKM) in SD/MI, interviews, and documentation in the form of a manuscript of the Minimum Competency Assessment (AKM) document. The results of the research on the readiness of class V teachers to the Minimum Competency Assessment (AKM) in SD/MI (1) The implementation of the Minimum Competency Assessment (AKM) in SD/MI has not been maximized because MI PUI Kuningan does not yet have a computer. (2) The readiness of class V teachers for the Minimum Competency Assessment (AKM) in SD/MI, teachers and principals have participated in socialization, tutoring, and training. (3) Supporting factors for the implementation of the Minimum Competency Assessment (AKM) in SD/MI in the form of evaluation. (4) The inhibiting factor for the implementation of the Minimum Competency Assessment (AKM) in SD/MI is not yet a computer at MI PUI Kuningan and has not yet obtained a library and reading books at SDN IV Kuningan.